Impact of psychosocial, behavioral and lifestyle factors on subjective cognitive complaints and perceived quality of life in a large cohort of Italian breast cancer patients - West, Thomas; Cavallero, Corrado; Ceccherini, Rita; Foladore, Silva; Generali, Daniele; Versace, Francesco; Scaggiante, Bruna (Frontiers in Psychology, 2022)
The impact of psychosocial and behavioral factors on Cancer Related Cognitive Impairment manifestations is still under debate. The study aims to determine the prevalence rate of cancer-related cognitive impairment in a cohort of Italian breast cancer patients and to evaluate the implication of specific behavioral factors. For these purposes, a total of 233 women (106 breast cancer patients and 127 age-matched controls without oncological diagnosis) completed a questionnaire investigating cognitive functionality (FACT-Cog v3.0), sociodemographic characteristics, clinical information, psychosocial and behavioral factors (cognitive reserve, sleep quality, dietary habits, physical activity). The results indicated a higher prevalence rate of subjective cognitive complaints in breast cancer patients (37%) compared to a representative sample of women in the same age group without an oncological diagnosis (p<.001). Moreover, breast cancer patients showed significantly lower levels of cognitive reserve (p<.05) and worse sleep quality (p<.01) compared to age-matched controls. Further analysis revealed that breast cancer patients reporting subjective cognitive complaints differed significantly from breast cancer patients without subjective cognitive complaints on measures of perceived cognitive abilities (p<.001) and on the impact of cognitive difficulties on the perceived quality of life (p<.01). Future studies are needed to examine behavioral directed interventions to prevent subjective cognitive deficits in breast cancer patients.